Syphilis in the context of HIV infection - Feller, L; Chandran, R; Marnewick, J C; Chikte, U M E; Gugushe, T S; Meyerov, R; Lemmer, J (SADJ (Houghton), 2011)
Both HIV infection and syphilis are sexually transmitted diseases, share the same risk factors for acquisition and often occur concurrently. Syphilis may promote HIV acquisition and transmission and HIV infection may alter the course and response of syphilis to treatment. Oral lesions may occur at any symptomatic stage during the course of a syphilitic infection, usually presenting as any one of a number of distinct clinical forms, but not infrequently with a variety of nonspecific clinical features, or clinical features mimicking other disease entities. In South Africa where HIV infection is epidemic, syphilis is prevalent. It is the purpose of this paper to review the interrelationship between syphilis and HIV infection, and the oral manifestations of syphilis.